Penguatan Soft Skills Siswa SMA Melalui Integrasi Kompetensi Keahlian SMK Dalam Implementasi Kurikulum Merdeka: Studi Kasus Di SMAN 2 Sandai: Strengthening the Soft Skills of High School Students Through the Integration of Vocational School Expertise in the Implementation of the Merdeka Curriculum: A Case Study at SMAN 2 Sandai - Sudiansyah, Sudiansyah; Sudianto, Iin; Sumarni, Rita (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research was motivated by the need to present a contextual and adaptive curriculum in remote areas, particularly for high schools in sub-district regions, by integrating vocational soft skills into learning based on the Merdeka Curriculum. The objective of this study was to design, implement, and validate an integrative curriculum based on vocational soft skills relevant to the needs of students and the professional world. This study employed a descriptive qualitative approach with a Research and Development (R&D) design using the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) framework. Data collection methods included observation, interviews, documentation studies, limited and extensive trials, as well as expert validation and Focus Group Discussions (FGD). Data sources consisted of the principal, teachers, students, and partners from vocational high schools and the business/industrial world (DUDI). Data analysis was conducted through reduction, categorization, interpretation, and member check validation. The results showed that this integrative curriculum was able to enhance student activeness, independence, creativity, and responsibility through thematic learning, collaborative projects, and participatory evaluation. In conclusion, this curriculum model is not only feasible and applicable but also relevant for widespread implementation as a form of character-based learning innovation and work readiness in remote areas.